α-Synuclein aggregation at low concentrations - Afitska, Kseniia; Fucikova, Anna; Shvadchak, Volodymyr V; Yushchenko, Dmytro A (Biochimica et biophysica acta. Proteins and proteomics, 2019)
BACKGROUND: Aggregation of the neuronal protein α-synuclein into amyloid fibrils is a hallmark of Parkinson's disease. The propensity of α-synuclein to aggregate increases with the protein concentration. For the development of efficient inhibitors of α-synuclein aggregation, it is important to know the critical concentration of aggregation (the concentration of monomeric protein, below which the protein does not aggregate). METHODS: We performed in vitro aggregation studies of α-synuclein at low concentrations (0.11-20 μM). Aggregation kinetics was measured by ThT fluorescence. Obtained aggregates were characterized using CD-spectroscopy, fluorescent spectroscopy, dynamic light scattering and AFM imaging. RESULTS: Monomeric α-synuclein at concentrations 0.45 μM and above was able to bind to fibril ends resulting in fibril growth. At the protein concentrations below 0.4 μM, monomers did not fibrillize, and fibrils disaggregated. In the absence of seeds, fibrils were formed only at monomer concentrations higher than 10 μM. At low micromolar concentrations, we observed formation of prefibrillar amyloid aggregates, which are able to induce fibril formation in α-synuclein solutions of high concentrations. CONCLUSIONS: The critical concentration of α-synuclein fibril growth is ~0.4 μM. Prefibrillar amyloid aggregates appear at concentrations between 0.45 and 3 μM and are an intermediate state between monomers and fibrils. Although morphologically different from fibrils, prefibrillar aggregates have similar properties to those of fibrils. GENERAL SIGNIFICANCE: We determined the critical concentration of α-synuclein fibril growth. We showed that fibrils can grow at much lower monomer concentrations than that required for de novo fibril formation. We characterized a prefibrillar intermediate species formed upon aggregation of α-synuclein at low micromolar concentration.
Keywords: Protein Aggregates; Circular Dichroism; fluorescenční spektrometrie; cirkulární dichroismus; Spectrometry, Fluorescence; Amyloid; alpha-Synuclein; Humans; proteinové agregáty; alfa-synuklein; lidé; amyloid